The Influence of Fear of Missing Out (FOMO), Social Influence, and Service Quality on Visitor Decisions at Cafe Taki in Palembang City - Putri Mulyanti; Budi Setiawan; Siti Komariah Hildayanti (International Journal of Economics and Management Research, 2026)
This study aims to analyze the effect of Fear of Missing Out (FOMO), Social Influence, and Service Quality on purchasing decisions of visitors at Cafe Taki. This research employs a quantitative approach using a survey method. The population consists of visitors to Cafe Taki Palembang City, with sample of 97 respondents selected using the accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with SPSS software. Partially Fear of Missing Out has a positive and significant effect on purchasing decisions, with a regression coefficient of 0.145, a t-value of 3.133, and a significance level of 0.002 < 0.05. Social Influence shows a positive and significant effect on purchasing decisions, with a regression coefficient of 0.385, a t-value of 7.590, and a significance level of 0.000 < 0.05. Furthermore, Service Quality has a positive and significant effect on purchasing decisions, indicated by a regression coefficient of 0.392, a t-value of 6.494, and a significance level of 0.000 < 0.05. Simultaneously, Fear of Missing Out, Social Influence, and Service Quality significantly influence purchasing decisions, as evi-denced by an F-value of 74.222 with a significance level of 0.000 < 0.05. The correlation coefficient (R) of 0.840 indicates a strong relationship between the independent variables and purchasing decisions, while the coefficient of determination (Adjusted R Square) of 0.696 reveals that 69.6% of the variation in pur-chasing decisions can be explained by the three independent variables, with the remaining percentage in-fluenced by other factors outside this study.